Prealamethicin F50 and related peptaibols from Trichoderma arundinaceum: validation of their authenticity via in situ chemical analysis. Issue 72 (25th September 2017) - Rivera-Chávez, José; Raja, Huzefa A.; Graf, Tyler N.; Gallagher, Jacklyn M.; Metri, Prashant; Xue, Ding; Pearce, Cedric J.; Oberlies, Nicholas H.
Abstract : A new technique was used to monitor the chemistry of fungal cultures in situ, thereby confirming authenticity of secondary metabolites. Abstract : In the field of natural products chemistry, a common question pertains to the authenticity of an isolated compound, i.e. are the interesting side chains biosynthesized naturally or an artefact of the isolation/purification processes? The droplet-liquid microjunction-surface sampling probe (droplet-LMJ-SSP) coupled to a hyphenated system (UPLC-UV-HRESIMS) empowers the analysis of natural product sources in situ, providing data on the biosynthetic timing and spatial distribution of secondary metabolites. In this study the droplet-LMJ-SSP was utilized to validate the authenticity of two new peptaibols (2 and3 ) as biosynthesized secondary metabolites, even though both of them had structural features that could be perceived as artefacts. Compounds2 and3 were isolated from the scaled up fermentation of Trichoderma arundinaceum (strain MSX70741), along with a new member of the trichobrevin BIII complex (1 ), and four known compounds (4–7 ). The structures of the isolates were established using a set of spectroscopic and spectrometric methods, and their absolute configurations were determined by Marfey's analysis. The cytotoxic activity of compounds1, 3, 4 and6 was evaluated against a panel of cancer cell lines, where cytotoxic activity in the single digit μM range was observed.